Association of HLA locus variant in Parkinson's disease - Zhao, Y.; Gopalai, A.A.; Ahmad-Annuar, A.; Teng, E.W.L.; Prakash, K.M.; Tan, L.C.S.; Au, W.L.; Li, H.H.; Lim, Shen Yang; Lim, Soo Kun; Chong, Yip Boon; Tan, Li Ping; et al. (Wiley, 2012)
A variant (rs3129882) in the genome-wide association study (GWAS)-linked variant [in the human leukocyte antigen (HLA) gene region] has been reported to associate with an increased risk of Parkinson's disease (PD) in Caucasian population. Studies among Chinese are limited. To address this, we analysed rs3129882 in a total of 1312 subjects of Chinese ethnicity from independent Asian centers comprising of 675 controls and 637 PD cases. The rs3129882 variant was associated with a decreased risk in our ethnic Chinese PD patients. Logistic regression analysis taking into consideration variables of age, gender and race showed that allele A reduced the risk of PD via a dominant model [odds ratio (OR)=0.77, 95% confidence interval (CI)=0.62, 0.96, p=0.018]. As HLA is a highly polymorphic region, it is possible that ethnic-specific effect or environmental agents may modulate the effect of this GWAS-linked locus in influencing the risk of PD. © 2012 John Wiley & Sons A/S.